Energy Performance and Thermal Comfort of Double-Skin and Single-Skin Facades in Warm-Climate Offices - Alibaba, Halil Z.; Ozdeniz, Mesut B. (Architectural Inst Japan, 2016)
The energy performance and thermal comfort of an office building with single and double skin facades, in a warm climate was studied using TAS software. A double-skin facade is an envelope construction that consists of two transparent surfaces separated by a cavity. The extra skin can reduce cooling demand in summer and heating demand in winter. It is concluded that in a warm climate office, a double skin facade can perform better than a single skin facade. In a warm climate a double skin facade fully provides heating and thermal comfort in winter. In a warm climate however its benefit in summer is limited. Further studies are needed to increase the performance of double skin facades in summer.
Keywords: double-skin facade; single-skin facade; thermal comfort; energy performance; TAS software